Polyoxomolybdate based ionic-liquids as active catalysts for oxidative desulfurization of simulated diesel - Mirante, Fatima (2019)
This work was partly funded through the Associate Laboratory for Green Chemistry- LAQV which is financed by national funds from FCT/MCTES (POCI-01-0145-FEDER-007265, UID/QUI/50006/2019) and CENIMAT, I3N (POCI-01-0145-FEDER-007688, UID/CTM/50025/2013), also financed by national funds through the FCT/MCTES, and when appropriate co-financed by the Fundo Europeu de Desenvolvimento Regional (FEDER) under the PT2020 Partnership Agreement. This work is funded by national funds (OE), through FCT – Fundação para a Ciência e a Tecnologia. European Social Fund through the program POPH of QREN. The authors also acknowledge the Portuguese Nuclear Magnetic Resonance Network (PTNMR).